2021
DOI: 10.1016/j.arth.2020.10.023
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Irradiated Cortical Strut Allograft Resorption Following Revision of Femoral Stems

Abstract: Background: Despite the widespread use of revision total hip arthroplasties using cementless stems and cortical strut allografts, graft resorption has not been explicitly studied. Methods: Between 2010 and 2018, 40 femoral strut grafts were used in the revision of femoral stems of 36 patients (18 males and 18 females; average age, 51.9 ± 12.9 years). The mean follow-up was 78.9 ± 37.3 months. Failure was defined as revision surgery for any reason and subsidence of greater than 5 mm. Results: The survival rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The previous research has reported the complete resorption of the allografts, and the resorption rate increases proportionally to the follow-up duration in the revision of femoral stems. However, the toughest bone would probably take longer to resorb and provide maximum stability [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…The previous research has reported the complete resorption of the allografts, and the resorption rate increases proportionally to the follow-up duration in the revision of femoral stems. However, the toughest bone would probably take longer to resorb and provide maximum stability [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using histological analysis, Kim et al found that patients with idiopathic ONFH or AIONFH have normal or nearly normal cancellous bone in the acetabulum and proximal femur, whereas GIONFH might be associated with more extensive osteonecrosis 21 . Patients with ONFH secondary to sickle-cell disease or steroid use have been found to have poor results of total hip arthroplasty when compared with agematched controls [22][23][24][25][26] . This heterogeneity may be related to the different biological effects on the bone tissue induced by different risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…Thank you for giving us the chance to reply to the letter to the editor regarding our article "High incidence of irradiated cortical strut allograft resorption following revision of femoral stems" published in JoA lately [1]. We would like to thank the readers for their important comments on the article.…”
mentioning
confidence: 97%